2015
DOI: 10.1016/j.vaccine.2014.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for developing an immunization strategy with enterovirus 71 vaccine

Abstract: Enterovirus 71 (EV71) is a common pathogen for hand, foot, and mouth disease (HFMD), which has significant morbidity and mortality, and for which children aged 6-59 months age are at highest risk. Due to lack of effective treatment options, control of EV71 epidemics has mainly focused on development of EV71 vaccines. Clinical trials have been completed on 3 EV71 vaccines, with trial results demonstrating good vaccine efficacy and safety. When EV71 vaccine is approved by China's national regulatory authority, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…The annual economic burden of EV-A71-associated HFMD amounts to US$161-323 million per year. 194 This figure is still optimistic since it does not take into account the fact that the number of annual EV-A71 cases is likely underestimated, or the number of HFMD cases caused by other enteroviruses, or the costs linked to sequelae and fatalities. Clinical trials have revealed that the administration of 400 units (1 mg) dose of EV-A71 vaccine twice achieved efficacy.…”
Section: Public Health Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual economic burden of EV-A71-associated HFMD amounts to US$161-323 million per year. 194 This figure is still optimistic since it does not take into account the fact that the number of annual EV-A71 cases is likely underestimated, or the number of HFMD cases caused by other enteroviruses, or the costs linked to sequelae and fatalities. Clinical trials have revealed that the administration of 400 units (1 mg) dose of EV-A71 vaccine twice achieved efficacy.…”
Section: Public Health Issuesmentioning
confidence: 99%
“…195 Another recent study reports that immunization with an EV-A71 vaccine would be cost-effective if vaccination costs were US$75 per dose for 90% efficacy. 194 With this profit margin and the new emerging vaccine markets in the Asia-Pacific region, the global vaccine companies should become interested in manufacturing monovalent, bivalent and ultimately multivalent HFMD vaccines.…”
Section: Public Health Issuesmentioning
confidence: 99%
“…39 However, in both arms the rate of adverse events was dramatically lower following booster injections, 40,41 as has been previously reported for other vaccines. 39,42 The Cochrane-Armitage analysis showed that in the vaccine group age was associated with the occurrence of adverse effects. In general, solicited adverse reactions were more frequent in younger patients, including fever, diarrhea, ANV, IDF, redness, swelling, and induration.…”
Section: Discussionmentioning
confidence: 99%
“…Краткое описание 3-й фазы испытаний и трех вакцин, полученных разными производителями Китая [38], представлены в таблице 1.…”
Section: вакцины на основе вирусоподобных частиц (Virus Like Particleunclassified